Academy establishes permanent training centre in Teesside, UK. Issue 12 (December 2016) - Unknown
Abstract : In the UK, the Academy of Joint Integrity, which is part of global sealing specialist Flexitallic, has established a permanent presence on Teesside and will deliver industry-standard flange assembly and sealing technology training courses from its new base in Middlesbrough.